Biological control of Rhamnus cathartica: is it feasible? A review of work done in 2002–2012. (19th December 2013) - Gassmann, A.; Tosevski, I.
Abstract Rhamnus cathartica (common buckthorn) is a shrub (or small tree) of Eurasian origin, which has become invasive in North America. Internal feeders and sap suckers were prioritized for biological control from over 30 specialized insects identified from the target plant in its native European range. Five leaf‐feeding moths were also considered for further investigations. Field observations and preliminary host range tests with the stem‐boring beetle Oberea pedemontana, the root‐boring moth Synanthedon stomoxiformis, the shoot‐tip‐boring moth Sorhagenia janiszewskae and the leaf‐feeding moths Ancylis apicella, A. unculana, Triphosa dubitata, Philereme transversata and P. vetulata confirmed that all of these species were lacking host specificity in no‐choice conditions. Choice oviposition tests carried out with most of the prioritized species to assess their ecological host range yielded unreliable results. Three psyllids, Trichochermes walkeri, Cacopsylla rhamnicolla and Trioza rhamni are promising in terms of host specificity, but are infected with the plant disease 'Candidatus Phytoplasma rhamni'. Fruit‐ or seed‐feeding insects may present the best potential for biological control of buckthorn in directly reducing seed set and thus seedling establishment. However, it was not possible to obtain adult fruiting trees of native North American Rhamnus species for testing. It is concluded that there are no promising arthropod agents based on what is known to date. Pathogens could offer new opportunities for biological control of R. cathartica in North America.